Effect of Modified Atmosphere on Bio-chemical Parameters and Shelf Life of Guava (Psidium guajava L.) cv. Hisar Safeda and L-49 - Bishnoi, Chetak; Sharma, R K; Siddiqui, S (Journal of Postharvest Technology, 2014)
An experiment was conducted to study the effect of different durations of modified atmosphere on bio-chemical parameters and shelf life of guava under ambient conditions. Fruits were packed in perforated polyethylene bags (LDPE) of thickness 300 gauge and then stored at 8ºC in BOD incubator for the periods 1, 2, 3 and 4 days. After respective durations of storage under MA at 8ºC, fruits were removed from MA and packed in CFB and stored at ambient temperature. Fruits were sampled at every day for various bio chemical pigments of guava. Among different durations of MA storage, the maximum total sugars and reducing sugars was recorded in the fruits stored for 0, 1 and 2 days and minimum in the fruits stored in MA for 4 days. The fruits stored in MA for different durations maintained high phenol contents and recorded maximum phenol in the fruit stored in MA for 4 days and minimum in control fruits. Higher retention of chlorophyll was recorded in the fruits stored in MA for 4 days while lesser carotenoids were recorded in fruit stored in MA for 4 days. Carotenoids content increased and chlorophyll content decreased with the increase in storage period in both the cvs Hisar Safeda and L-49 (Sardar).